Better safe than sorry – a qualitative study of multidisciplinary use of the V-RISK-10 in assessing patients with psychosis - Seierstad, Andreas; Bruu, Bente Kristin; Schjøtt-Pedersen, Olivia; Løvgren, André; Lockertsen, Øyvind (Frontiers in Psychiatry, 2025)
BackgroundViolence in mental health inpatient settings is a recognized challenge and structured professional judgement (SPJ) tools might aid clinicians in assessing risk and tailoring preventive interventions. Multidisciplinary collaboration when completing SPJ tools have been considered a feasible approach to reducing bias, increasing transparency and linking risk assessment with risk management. This study aims to explore experiences among health care professionals on multidisciplinary use of the SPJ tool violence risk screen V-RISK-10 in a closed psychosis ward.MethodsData were collected by means of semi-structured interviews with a heterogeneous sample of health care professionals (n=8) recruited from a psychosis ward at a psychiatric hospital in Norway. Snowball sampling was utilized to recruit participants who had experiences relevant for the study’s aim. Transcribed interviews were analyzed using thematic analysis.ResultsThree overarching themes were identified: 1) attitudes toward screening for possible violence, 2) attitudes towards using the V-RISK-10 and 3) attitudes toward multidisciplinary use of the V-RISK-10. In summary, subthemes revealed that screening was perceived as important, and participants perceived the tool in question as quick and systematic yet noted that missing information on the day of admittance was problematic. Important discussions were sparked and targeted interventions initiated as a result of multidisciplinary collaboration.DiscussionStaff attitudes have been described as a potential barrier for the use of SPJ tools, yet little empirical knowledge exists on the beliefs behind staff attitudes. Our study sheds light on what staff found helpful and not helpful when using the V-RISK-10. These findings can aid implementation of SPJ tools, especially screening instruments, because they highlight possible pathways toward increased use for health care professionals.